Respuesta :

sali07

Answer:

use elimination

8x-3y=2

-8x-5y=46

8x cancel out

-5y-3y= -8y= 48

48/-8= -6y

Step-by-step explanation:

ANSWER= -6y

Answer:

  (x, y) = (-2, -6)

Step-by-step explanation:

The coefficients of x are opposites, so the variable x can be eliminated by adding the equations together:

  (8x -3y) +(-8x -5y) = (2) +(48)

  -8y = 48 . . . . . simplify

  y = -6 . . . . . . . divide by -8

Use this value in either equation to find x.

  8x -3(-6) = 2

  8x = -16 . . . . . . subtract 18

  x = -2 . . . . . . .  divide by 8

The solution to the system of equations is (x, y) = (-2, -6).

_____

I like a graphing calculator for verifying results.

Ver imagen sqdancefan
ACCESS MORE